Interplay of sociocultural factors, health literacy and well-being among African asylum seekers and refugees in Asia: A systematic review - Padmore Adusei Amoah; Edward Kwabena Ameyaw; Genevieve Ataa Fordjour (Journal of Migration and Health, 2024)
Background: There are many African asylum seekers and refugees (AAR) in Asia. However, little research has been conducted on their well-being within the sociocultural milieu. This systematic review explores the characteristics of AAR's psychological and mental well-being and how their acculturation practices, social networks and support (i.e. social capital), health-related knowledge and skills (i.e., health literacy) influence their psychological and mental well-being. Methods: The study included relevant peer-reviewed articles from any Asian country/region, published in English. No date restriction was applied. Five databases (i.e. Scopus, PubMed, Web of Science, PsycINFO, and CINAHL) were searched for studies conducted about AAR from any of the 54 African countries and residing in any of the 51 Asian countries. Following a predefined inclusion criteria and quality assessment, nine articles were included in this study. Narrative synthesis approach was used to analyse the articles. Results: It was found that AARs face significant challenges that culminate in poor psychological and mental well-being, including conditions such as depression and discontent with their lives. Notwithstanding, being in a safe place made some of them optimistic about their future. However, many AARs had difficulties adjusting to the host culture. They had limited awareness of the prevailing health system and services and faced restrictions on their rights to social services, partly because of difficulty obtaining appropriate information. The few social bonds and bridges they possessed enabled them to develop a sense of belonging and protected them from psychological distress. However, problematic social relationships increased the chances of poor health-related outcomes. Conclusion: The psychological and mental well-being of AAR in Asia is concerning. Hence, more research on how critical health determinants (i.e. social capital, health literacy and acculturation processes from this study) directly and interactively influence their well-being across age cohorts. Given their roles in promoting AAR's well-being, appropriate interventions to improve those critical health determinants are also sorely needed.